2009
DOI: 10.3390/v1031295
|View full text |Cite
|
Sign up to set email alerts
|

Viral Hybrid Vectors for Somatic Integration - Are They the Better Solution?

Abstract: The turbulent history of clinical trials in viral gene therapy has taught us important lessons about vector design and safety issues. Much effort was spent on analyzing genotoxicity after somatic integration of therapeutic DNA into the host genome. Based on these findings major improvements in vector design including the development of viral hybrid vectors for somatic integration have been achieved. This review provides a state-of-the-art overview of available hybrid vectors utilizing viruses for high transduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 143 publications
(181 reference statements)
0
13
0
Order By: Relevance
“…In contrast to other previously described adenoviral hybrid-vector systems, 3,37 our vector releases a genetic element that can be maintained episomally after excision based on FLPe recombination. In this study, we demonstrated that the plasmid replicon pEPito can function as a substrate for FLPe recombination and, at the same time, maintain its function as a plasmid replicon for stable transgene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other previously described adenoviral hybrid-vector systems, 3,37 our vector releases a genetic element that can be maintained episomally after excision based on FLPe recombination. In this study, we demonstrated that the plasmid replicon pEPito can function as a substrate for FLPe recombination and, at the same time, maintain its function as a plasmid replicon for stable transgene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Since that time, several studies have been developed on hybrid transposase systems (reviewed in Refs. [60,61]) that use adenovirus [62][63][64], adeno-associated virus [65], baculovirus [66], or nonintegrative lentivirus [67,68] particles.…”
Section: Viral Hybrid Systemsmentioning
confidence: 99%
“…Hybrid Ad systems have been described with elements incorporated from adeno-associated virus (AAV), retrovirus, sleeping beauty (SB) transposons, L1 retrotransposons, or PhiC31 integrase. 4 While each of these strategies successfully facilitates genomic integration of cargo genes, efficiencies are typically below 1% of transduced cells. [5][6][7][8] A hybrid Ad-lentiviral system has achieved an in vivo stable transduction rate of 20-30% in mouse liver, 9 although the efficiency was likely influenced by the immunodeficient nature of the mice that were used.…”
Section: Introductionmentioning
confidence: 99%